IMPROVING STUDENT ARABIC LANGUAGE CAPABILITIES WITH A MULTI-STRATEGIC APPROACH - Ru’iya, Sutipyo; Thonthowi (Idaarah: Jurnal Manajemen Pendidikan, 2022)
This research is a field research with a descriptive qualitative approach. The purpose of this study is to reveal the efforts of Arabic language teachers in overcoming students’ difficulties in student learning so that students achieve the specified competencies. The subjects of this study were Arabic teachers at Madrasah Tsanawiyah Darul Ulum Muhammadiyah (MTs DU M) Galur Yogyakarta. Collecting data through structured observations and in-depth interviews with Arabic teachers, and several students to compare the data obtained. Data analysis starts from data reduction, data presentation, and drawing conclusions. The results of this study are teachers at MTs DU M Galur classified as professional teachers. Teachers are skilled in responding to individual differences (individual differences) in students and students’ conditions are very heterogeneous, teachers group students according to their basic abilities, develop material on the applied curriculum that composes material that is happening among students. Arabic teachers apply several methods and learning strategies that are supported by the use of several media and tools available at the madrasa. Finally, the ability achieved by students during Arabic learning is classified as very high, reaching 97-99% of students achieving competence by applying authentic evaluation.